ANALYSIS KARATE TECHNIQUE SKILL WOMEN KUMITE IN SEA GAMES 2017 - Azizah, Arbaatin Nur (Jurnal Kesehatan Olahraga, 2019)
Karate is a sport of martial arts originating from Japan, according to Ivan (2012: 20) karate comes from twowords kanji